Goatweed Biology and Control in Pastures - Brent A. Sellers (EDIS)
SS-AGR-299, a 3-page illustrated fact sheet by Brent A. Sellers, describes the biology and control of this perennial plant, also known as sweet broom and licorice weed, that is becoming a serious problem in Florida pastures. Published by the UF Department of Agronomy, February 2008.